EFEK APLIKASI PUPUK KANDANG KAMBING DAN PUPUK N, P, K TERHADAP SIFAT KIMIA TANAH, SERAPAN P, PERTUMBUHAN DAN PRODUKSI SAWI HIJAU (Brassica juncea L.) DI KECAMATAN TULANGAN, KABUPATEN SIDOARJO - Aisyah Hairani Aulia; Retno Suntari (Departemen Tanah, Fakultas Pertanian, Universitas Brawijaya, 2023)
The high demand for mustard greens from consumers in Sidoarjo has forced farmers to increase their production. One of the efforts made is to provide excessive N, P, and K fertilizers. This study aimed to analyze the effect of the combined application of goat manure and N, P, K on growth, yield, P uptake, and soil chemical properties. Six treatments and three replications arranged in a randomized block design. The results showed that the combination of goat manure and N, P, K fertilizer had a significant effect (p<0.05) on plant height, number of leaves, plant fresh weight, total plant P, soil pH, soil organic C, soil total N, soil C/N ratio, and soil total P, but not significantly different (p>0.05) on plant dry weight, P absorption, and available P of the soil. The combination of goat manure and N, P, K fertilizer increased plant height from 36.4 cm to 50 cm (+37.4%), number of leaves from 18 to 43 leaves (+143.8%), fresh weight from 92 g to 310 g (+237%), dry weight from 10.8 g to 14.1 g (+30.6%), total crop P from 1.4% to 1.45% (+3.6%), P uptake from 15.1 g to 20.5 g (+35.2%), organic C from 0.97% to 1.25% (+28, 9%), total N from 0.35% to 0.42% (+20%), C/N ratio from 2.77 to 2.97 (+7.2%), total P from 18.9 mg 100 g-1 to 36.6 mg 100 g-1 (+26.6%), and available P from 4.22 ppm to 6.24 ppm (+49.9%).